Cannabis, Impaired Driving, and Road Safety: An Overview of Key Questions and Issues - Brands, Bruna; Di Ciano, Patricia; Mann, Robert E. (Frontiers in Psychiatry, 2021)
The road safety impact of cannabis has been a topic of much discussion and debate over the years. These discussions have been revitalized in recent years by initiatives in several jurisdictions to legalize non-medical cannabis. Canada became the second country to legalize non-medical cannabis use in October, 2018, preceded by Uruguay in December 2013. Road safety concerns were key issues in the Canadian government’s deliberations on the issue. In this paper, we identify several key questions related to the impact of cannabis on road safety, and provide a consideration of the relevant literature on these questions. These questions cover several perspectives. From an epidemiological perspective, perhaps the central question is whether cannabis use contributes to the chances of being involved in a collision. The answer to this question has evolved in recent years as the ability to conduct the relevant studies has evolved. A related question is the extent to which cannabis plays an important role in road safety, and recent research has made progress in estimating the collisions, injuries and deaths that may be attributed to cannabis use. Several questions relate to the behavioural and pharmacological effects of cannabis. One central question is whether cannabis affects driving skills in ways that can increase the chances of being involved in a collision. Another important question is whether the effects of the drug on the driving behaviour of medical users is similar to, or different from, the effects on non-medical users and whether there are sex differences in the pharmacological and behavioural effects of cannabis . Other important questions are the impact of tolerance to the effects of cannabis on road safety as well as different routes of administration (e.g. edibles, vaped). It remains unclear if there is a dose-response relationship of cannabis to changes in driving. These and other key questions and issues are identified and discussed in this paper.